The Model of Problem Solving in Mathematics Learning in Indonesia - Darmadi., D (Prosiding Konferensi Nasional Penelitian Matematika dan Pembelajarannya, 2019)
Most in learning mathematics in Indonesia, students are familiarized with the writedown is known, asked, and the answer to resolving the issue. Conditioning is different from the theories of problem-solving, such as Polya provide problem resolution with understand, plan, implement, and re-evaluate it (looking backward). The difference between theory and practice applied mainly drew attention in the study of logic and the set. Results of the study indicate that there are two modes of representation of problem solving in Indonesia. The first model of mathematical problem solving is writing the note, asked, and answered. The second model is the solution to math problems in Indonesia is taking the example, will be demonstrated, and evidence.